2016
DOI: 10.1177/0363546516663931
|View full text |Cite
|
Sign up to set email alerts
|

Physical Risk Factors for a Medial Elbow Injury in Junior Baseball Players: A Prospective Cohort Study of 353 Players

Abstract: The incidence of an initial medial elbow injury was 22.1%. Age, number of throws per day, thoracic kyphosis angle, and elbow extension deficit are newly discovered risk factors related to physical function. Improvement of the posture and early detection of a silent elbow extension deficit may prevent a medial elbow injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 31 publications
(61 reference statements)
3
127
0
1
Order By: Relevance
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
“…Until now, various injury prevention programs have been carried out to try to prevent elbow injury in baseball players. These include studies of pitching form using a three-dimensional motion analysis system, [29][30][31][32] studies of the relationship between physical functions and injuries, 22,33 basic studies on the elbow joint by evaluation such as using ultrasound scanning or radiographs, [10][11][12][13][14][15][16][17][18] and encouraging a limitation of the number of pitches in a game. 20,34 However, although these prevention projects have been carried out, it is reported that the number of UCL reconstruction surgeries in recent years has increased, 35 suggesting that these preventative measures are not effective or are not being used effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unclear what the influences are on the elbow extension deficit observed in this study and what influences directly change the mechanical stress on the elbow during throwing. In a prospective survey of elementary school baseball players, Sakata et al 21) suggested that if the elbow extension deficit is more than 5°, it is a risk factor for the occurrence of elbow injury later. Therefore, decreased elbow extension ROM of the throwing side may have occurred before the occurrence of pain; and it is necessary to prospectively evaluate junior high school baseball players in the future.…”
Section: Discussionmentioning
confidence: 99%